City information modeling as a tool for problem identification and solution in urban spaces development / Gregorius A Gegana A, Felia Srinaga and Julia Dewi - Gegana A, Gregorius A; Srinaga, Felia; Dewi, Julia (Universiti Teknologi MARA, Perak, 2022)
Many of our decisions in urban planning depend on details of our immediate surroundings and require information about the specific place on Earth. In this digital collaboration era, problems and information about cities and regions can extend rapidly. Therefore, architects and urban designers need tools that can capture this information immediately to help in urban evaluation and design. Building Information Modeling (BIM) has changed the way architects and designers work and collaborate in building design. This swift collaboration workflow should be applied in urban and infrastructure design byutilising BIM tools that can harness the data from Geographic Information System (GIS), therefore conceiving the terms City Information Modeling. This paper discusses how the sutilisation of City Information Modeling tools has been explored and workflow as well as integration that can be improved further for evaluating urban space problems and solutions. The study is run through two courses held at the Department of Architecture Universitas Pelita Harapan that explor the tools to harness GIS data, sanalyse urban spatial, and collaborate in urban space planning. In these courses, students take study cases in two places: Jakarta and Medan, which has an old city area that has a significant impact on overall city development. The research looks at workflow, sutilisation of the software through students' learning outcomes, and students' work.